Thermal Field Analysis of Oblique Machining Process with Infrared Image for AA6063-T6 - Abdulateef, Osamah F.; Salman, Lara A. (Al-Khwarizmi Engineering Journal, 2015)
Abstract Metal cutting processes still represent the largest class of manufacturing operations. Turning is the most commonly employed material removal process. This research focuses on analysis of the thermal field of the oblique machining process. Finite element method (FEM) software DEFORM 3D V10.2 was used together with experimental work carried out using infrared image equipment, which include both hardware and software simulations. The thermal experiments are conducted with AA6063-T6, using different tool obliquity, cutting speeds and feed rates. The results show that the temperature relatively decreased when tool obliquity increases at different cutting speeds and feed rates, also it is found that the mean tool rake face temperature distribution decreases with increase of tool obliquity. The result also show that the maximum error between the predicted and measured temperatures by IR camera was between 6-27 °C. Keywords: Infrared, Deform-3D, tool obliquity, turning.